ANALISIS LAYANAN BK DI SMK GAMALIEL PADA MASA PANDEMI COVID-19 - Sri Rahayu, Dwi (Widya Warta, 2020)
The changes in learning system due to the spread of Corona Virus Disease (Covid-19) have an impact on the provision of guidance and counseling services. This study aimed (1) to find out the media which were used to carry out online guidance and counseling services, (2) to find out the obstacles which were experienced when implementing guidance and counseling services during the Covid-19 pandemic at SMK Gamaliel 1 Madiun, (3) to find out the alternatives which were implemented by the counselors of guidance and counseling services. The respondents were all of the guidance and counseling teachers in SMK Gamaliel 1 Madiun consisted of three persons. Data were collected using questionnaires. Data analysis used the model of Miles and Huberman. The results obtained were (1) the media used in online guidance and counseling services during Covid-19 pandemic period were Whatsapp, Email, Zoom, Teams, Google Meet, and Google Classroom, (2) the difficulties experienced in implementing online guidance and counseling services were unstable networks, internet usage that took up the quota, and the challenges in creating a conducive service atmosphere during Work From Home, (3) the alternatives implemented by the counselors were studying the applications other than Whatsapp and giving more emphasis on the principles of guidance and counseling.